DESKRIPSI PEMAHAMAN KONSEP MATEMATIKA PADA MATERI BANGUN RUANG MENGGUNAKAN METODE DISKUSI KELOMPOK - Fauzi Mulyatna; Aziziyah Zahra Jinan; Celia Nurul Amalina; Eka Putri Widyawati; Gusti Alif Aprilita; Huri Suhendri (TRANSFORMASI, 2023)
This study aims to describe students' understanding of mathematical concepts in learning using the group discussion method on geometric material. The research was conducted qualitatively research with a descriptive approach. The research was conducted at SMPN 259 Jakarta, with 35 class VII-I students as subjects. Data collection was carried out by tests, learning observations, and interviews with students and teachers. The test is ini the form of multiple choices and is foolowed up with questions related to the process of finding the final answer. Indicators of understanding the concept are not only limited to correct or incorrect multiple-choice answers, but descriptions of the explanation of the process of answering them. Interviews with students were conducted to determine understanding of the concept in solving problems. Interviews with teachers were conducted to find out the concept had been given as a whole, not just to obtain the final result. The difficulties that are often found by students are not understanding the spatial context, too focused on formulas, and not understanding precisely the subject that is included in the low concept understanding criteria which is still at 49%. The description shows that the subject does not understand the meaning of using the formula and the accuracy in its use. So it becomes important for teacher to emphasize the context of the concepts represented in the formula, not just limited to calculation procedures.